Timeline reminder system bot and telegram assistant chatbot for a university student and lecturer - Haqimi, Nur Azizul; Kusuma, Rendra Tri (Journal of Soft Computing Exploration, 2023)
This research relates to the development of a chatbot application to help lecturers and students in the D3 Informatics Engineering study program remember schedules of activities and answer questions related to the study program. The background of this research is due to the difficulties of lecturers in managing activity schedules and answering questions that come from D3 Informatics Engineering study program students effectively and efficiently. This shows that having chatbot reminder and assistant applications will be very useful for study programs. The purpose of this research is to develop a bot and chatbot application that can help lecturers and students at Diploma 3 Informatics Engineering in managing activity schedules and answering questions related to study programs. The research method used is the Waterfall system development method, which is a type of System Development Life Cycle (SDLC). This method follows the sequential stages of system development starting from requirements analysis, system design, implementation, testing and maintenance. In this study, the chatbot application was developed using the Golang programming language, Codeigniter4 as the dashboard platform.